Klasterisasi Jurusan SMK Untuk Peningkatan Kerjasama Antara BLK Dengan SMK Di Blora - Adiyah Mahiruna; Alya Masitha; Lathifatul Aulia; Arista Fitri Diana; Rowiyani; Alvin Muslikhun; Mukhlidin (Jurnal Atma Inovasia, 2026)
The Minister of Primary and Secondary Education (Mendikdasmen), Abdul Mu'ti, emphasized the new policy direction for the development of Vocational High School (SMK) education. The Minister explained that future SMK graduates are expected to have not only diplomas, but also skills certificates that support their competitiveness and readiness in the world of work. The Ministry of Primary and Secondary Education (Kemendikdasmen) is collaborating with the Ministry of Manpower to establish Vocational Training Centers (BLK). The Community BLK Program is a government effort to increase the distribution of job training institutions. Higher Education Institutions (PT) in Indonesia are also given certain authorities to provide and organize study programs at various levels (diploma, bachelor's, master's, doctoral, specialist profession) according to the capabilities of each PT and industry needs. The ITESA Muhammadiyah Semarang team of community service lecturers will bridge the competency clustering in SMK with the clustering of human resource needs in the industry.